Seismic Response Mitigation of Steel-Concrete Hybrid Wind Turbine Tower by Using Isolation Bearings and Distributed Tuned Mass Dampers - Dongliang Zhang; Tianhao Li; Kun Fu; Ziteng Peng; Chu Zhao; Cirong Huang (Shock and Vibration)
The onshore wind turbines are gradually developing with the aim of large single-unit capacity, large impeller diameter, and higher towers. The steel–concrete hybrid tubular tower structure is the mainstream structure of high-hub towers, whose lower part is a concrete tower tube and the upper part a steel tower tube. Also, there is no doubt that more and more wind turbines will work in harsh environments and seismic hazard zones. Based on the abovementioned two points, it is necessary to mitigate the dynamic responses of onshore wind turbines to ensure the safety of these structures. This paper studied the base-isolated method, story-isolation method, and three types of tuned mass dampers damping method: single tuned mass dampers (STMDs), multiple tuned mass dampers (MTMDs), and distributed-tuned mass dampers (D-MTMDs), to explore the response characteristics of the steel–concrete hybrid tubular tower under seismic loads. The results show that the base-isolated structure can greatly reduce the bending moment and shear response of the upper steel tower tube, while the story-isolated structure has a very good effect on reducing the structural displacement response. In the three tuned mass dampers damping method, D-MTMDs have stable and effective control capacity, compared with STMD and MTMDs.